Regret Aversion and Decision Process Quality: Effect of Regret Salience on Decision Process Carefulness - REB, Jochen (Institutional Knowledge at Singapore Management University, 2008)
A considerable amount of past research has examined the effects of regret aversion on which options decision makers choose. However, past research has largely neglected to address the effect of regret aversion on the decision process. We conducted five experiments to examine the effect of making regret salient on decision process quality. We predicted that increased regret aversion would lead to more careful decision processing. The results consistently supported this prediction across the different decision situations, incentive structures, regret salience manipulations, and dependent variables used. In all experiments making regret salient led decision makers to take significantly longer to reach a decision. In Studies 2a, 2b, and 4 it also led participants to collect significantly more information before making a choice. Implications and future directions are discussed.